Audiovisual translation : - Díaz-Cintas, Jorge. (St. Jerome Pub., 2007)
The individual chapters cover the rules of good subtitling practice, the linguistic and semiotic dimensions of subtitling, the professional environment, technical considerations, and key concepts and conventions, providing access to the core skills and knowledge needed to subtitle for television, cinema and DVD. Also included are graded exercises covering core skills. "Audiovisual Translation: Subtitling" can be used by teachers and students as a coursebook for the classroom or for self-learning.It is also aimed at translators and other language professionals wishing to expand their sphere of activity.